# Reading Math & Its History (02)

## Greek Geometry

Reading Math & Its History (01) The Theorem of Pythagoras
Reading Math & Its History (02) Greek Geometry
Reading Math & Its History (03) Greek Number Theory
Reading Math & Its History (04) Infinity in Greek Mathematics

# 2.1 The Deductive Method

## Exercise 2.1.1

Common Notion 1:
Things which are equal to the same thing are also equal to one another.

a ≈ b and b ≈ c => a ≈ c

Common Notion 4:
Things which coincide with one another are equal to one another.

a ≈ a

## Exercise 2.1.2

Euclid uses “one another” which means a ≈ b and b ≈ a.

# 2.2 The Regular Polyhedra

## Exercise 2.2.1

The cube is in blue:

`Let half of cube side OR = 1, thenRP = √2OP = √(OR^2 + RP^2) = √3OP/OR = √3/1 = √3`

The octahedron is in blue:

`Let OQ = 1, thenthe shortest distance to any side OP = 1/√2PQ = √(OP^2 + OQ^2) = √((1/√2)^2 + 1^2) = √3/√2 OR * PQ = OP * OQOR = OP * OQ / PQ = 1/√2 * 1 / (√3/√2) = 1/√3OQ / OR = √3`

## Exercise 2.2.2

Icosahedron:

Pacioli’s construction with sides 1 and (1 + √5)/2:

`τ = (1 + √5)/2ττ = (6 + 2√5)/4 = (3 + √5)/2 = τ + 1BC = 1AD = τ/2ED = τ/2 - 1/2AE^2 = ED^2 + AD^2 = (τ/2 - 1/2)^2 + (τ/2)^2AC^2 = AE^2 + EC^2 = (τ/2 - 1/2)^2 + (τ/2)^2 + (1/2)^2= (ττ - 2τ + 1)/4 + ττ/4 + 1/4= ττ/2 - τ/2 + 1/2= (τ + 1)/2 - τ/2 + 1/2= 1AC = 1AB = AC = BC = 1`

## Exercise 2.2.3

A = (-1, 0, τ)
B = (-τ, 1, 0)
C = (-τ, -1, 0)

Each golden rectangle has 3 symmetric points.
(±1, 0, ±τ)
(±τ, ±1, 0)
(0, ±τ, ±1)

## Exercise 2.2.4

circumradius = OA = √(ττ + 1) = √(τ + 1)

## Exercise 2.2.5

F is the centre of ∆ABC.

`OE = AD = τ = (1 + √5)/2OD = 1ED = τ - 1AE = √(AD^2 + ED^2) = √(2ττ - 2τ + 1)= √(2(τ + 1) - 2τ + 1)= √3AF = (2/3)AE = 2/√3OA^2 = OD^2 + AD^2 = ττ + 1 = τ + 2OF = √(OA^2 - AF^2) = √(τ + 2 - 4/3) = √(τ + 2/3) OA/OF = √(τ + 2)/√(τ + 2/3) = 3√(τ + 2)/√(9τ + 6)`

## Exercise 2.2.6

`(3√(τ + 2)/√(9τ + 6))^2= 9(1/2 + √5/2 + 2)/(9/2 + 9√5/2 + 6)= 9(5 + √5)/(21 + 9√5)= 9(5 + √5)(21 - 9√5)/(441 - 405)= 9(60 - 24√5)/36= 15 - 6√5= 3(5 - 2√5)(√(3(7 - 4τ)))^2= 3(7 - 2 - 2√5)= 3(5 - 2√5)(√(15/(4τ + 3)))^2= 15/(2 + 2√5 + 3)= 15/(5 + 2√5)= 15(5 - 2√5)/(25 - 20)= 3(5 - 2√5)`

## Exercise 2.2.7

Dodecahedron:

Dual dodecahedron:

`circumradius of dual dodecahedron= inradius of icosahedron= OF = √(τ + 2/3)= (1/3)√(9τ + 6)`
`A = (-1, 0, τ) B = (-τ, 1, 0)C = (-τ, -1, 0)D = (0, -τ, 1)E = (1, 0, τ)F = (0, τ, 1)`

The centre of ∆ABC = (A + B + C)/3
The centre of ∆ACD = (A + C + D)/3
The centre of ∆ADE = (A + D + E)/3
The centre of ∆AEF = (A + E + F)/3
The centre of ∆AFB = (A + F + B)/3

The centre of the pentagon of the above 5 centres:

`(1/5)((A + B + C)/3 + (A + C + D)/3 + (A + D + E)/3 + (A + E + F)/3 + (A + F + B)/3)= (1/15)(5A + 2B + 2C + 2D + 2E + 2F)= (1/15)(-5 - 4τ + 2, 0, 5τ + 2τ + 4)= (1/15)(-4τ - 3, 0, 7τ + 4)= (4τ + 3)/15(-1, 0, τ)`

`((4τ + 3)/15)√(ττ + 1) = ((4τ + 3)/15)√(τ + 2)`

## Exercise 2.2.8

`circumradius/inradius= (1/3)√(9τ + 6) / (((4τ + 3)/15)√(τ + 2))= 5√(9(1 + √5)/2 + 6) / ((4(1 + √5)/2 + 3)(√((1 + √5)/2 + 2)))= 5√(9 + 9√5 + 12) / ((2 + 2√5 + 3)√(5 + √5))= 5√(21 + 9√5) / ((5 + 2√5)√(5 + √5))= 5√(3(7 + 3√5)) / ((5 + 2√5)√(5 + √5))= 5√(3(7 + 3√5))√(5 - √5) / ((5 + 2√5)√(5 + √5)√(5 - √5))= 5√(3(7 + 3√5)(5 - √5)) / ((5 + 2√5)√20)= 5√(3(7 + 3√5)(5 - √5)) / (2(5√5 + 10))= √(3(7 + 3√5)(5 - √5)) / (2(√5 + 2))= √(3(7 + 3√5)(5 - √5))(√5 - 2) / (2(√5 + 2)(√5 - 2))= √(3(7 + 3√5)(5 - √5)(9 - 4√5)) / 2= √(3(20 + 8√5)(9 - 4√5)) / 2= √(3(5 + 2√5)(9 - 4√5))= √(3(5 - 2√5))which is same as the result of Exercise 2.2.6√(15/(4τ + 3))= √(15/(2 + 2√5 + 3))= √(15/(5 + 2√5))= √(15(5 – 2√5)/(25 – 20))= √(3(5 - 2√5))`

## Icosahedron I

`S = 20 ∆ABCV = 20 (1/3) ∆ABC * OFS/V = (1/3)/OF = (1/3)/inradius`

## Dodecahedron D

Each face is same as pentagon BCDEF.

`S = 12 BCDEFV = 12 BCDEF * (1/3)inradiusS/V = (1/3)/inradius`

In Exercise 2.2.8 we already show that circumradius/inradius is same for dodecahedron and icosahedron. So with same circumradius, SofI/VofI = SofD/VofD, and we get

suface area D / surface area I = volume D / volume I

# 2.3 Ruler and Compass Constructions

## Exercise 2.3.1

`L / L1 = L2 / 1L = L1 * L2`
`L1 / L2 = L / 1L = L1 / L2`

## Exercise 2.3.2

`∆BAD is similar to ∆ACDBD / AD = AD / DCDC = 1BD = AD * ADBD = lAD = √l`

## Exercise 2.3.3

`∆ABP ≈ ∆DCPAB / DC = BP / DPAB = xDC = 1BP = 1DP = DB - BP = x - 1x / 1 = 1 / (x - 1)`

## Exercise 2.3.4

`x(x - 1) = 1xx - x - 1 = 0x = (1 ± √(1 + 4))/2x = (1 + √5)/2`

# 2.4 Conic Sections

## Exercise 2.4.2

Let OF1 = OF2 = c. Assume PF1 + PF2 = constant. When point P(x, y) moves to X axis, it’s easy to see that that constant = 2a. Similarly when P moves to Y axis, it’s easy to see that each of red lines has length a. So we get a² = b² + c².

Now we just need to check whether x²/a² + y²/b² = 1 and a² = b² + c² are equivalent.

`PF1 + PF2 = 2a√((x + c)^2 + yy) + √((x - c)^2 + yy) ?= 2a√((x + c)^2 + yy) ?= 2a - √((x - c)^2 + yy)(x + c)^2 + yy ?= 4aa + (x - c)^2 + yy - 4a√((x - c)^2 + yy)2cx ?= 4aa - 2cx - 4a√((x - c)^2 + yy)4a√((x - c)^2 + yy) ?= 4aa - 4cxa√((x - c)^2 + yy) ?= aa - cxaa((x - c)^2 + yy) ?= (aa - cx)^2aa(xx - 2cx + cc + yy) ?= a^4 - 2aacx + ccxxaaxx + aacc + aayy ?= a^4 + ccxx`

Cool, all terms with c are gone, leaving c² terms. Let’s continue.

`cc = aa - bbaaxx + aa(aa - bb) + aayy ?= a^4 + (aa - bb)xxaaxx + a^4 - aabb + aayy ?= a^4 + aaxx - bbxx-aabb + aayy ?= -bbxxbbxx + aayy ?= aabbxx/aa + yy/bb = 1`

## Exercise 2.4.3

The sum of 2 sides of a triangle is greater than the 3rd side. So FPF2' < F1P’F2'.

## Exercise 2.4.4

F1PF2 = F1PF2' < F1P’F2. Angles 1, 2 and 3 are same.

# 2.5 Higher-Degree Curves

## Exercise 2.5.1

Cissoid

`OM / QN = OR / QROR = 1XX + YY = 1QN = √(1 - xx)OM = QN * OR / QR = √(1 - xx) / (1 + x)Y = (OM/OR)X - OMY = (OM)X - OM = OM(X - 1)Y = (√(1 - xx) / (1 + x))(X - 1)`

## Exercise 2.5.2

P is the intersection of line NR and line X = x. So y is Y when X = x.

`y = (√(1 - xx) / (1 + x))(x - 1)yy = ((1 - xx)/(1 + x)^2)(x - 1)^2yy = ((1 - x)/(1 + x))(x - 1)^2yy(1 + x) = (1 - x)^3y^2(1 + x) = (1 - x)^3`

cardioid

## Exercise 2.5.4

Review some trigonometrical identities first using a unit circle.

`sin2θ = CD = ACsinθ = (ABcosθ)sinθ = 2cosθsinθcos2θ = OD = AD - AO = ACcosθ - 1 = (ABcosθ)cosθ - 1 = 2(cosθ)^2 - 1`

Q is a point on cardioid. a = 1, φ = θ.

`x = OR + RQcosθy = RQsinθRQ = 2RN = 2SM = 2(OM - OS) = 2(1 - ORcosθ) = 2(1 - cosθ)x = 1 + 2(1 - cosθ)cosθ = 1 + 2cosθ - 2(cosθ)^2 = 2cosθ - cos2θy = 2(1 - cosθ)sinθ = 2sinθ - 2cosθsinθ = 2sinθ - sin2θ`

## Exercise 2.5.5

`x = 1 + 2(1 - cosθ)cosθ = 1 + 2cosθ - 2(cosθ)^2y = 2(1 - cosθ)sinθ = 2sinθ - 2cosθsinθ = 2sinθ(1 - cosθ)(xx + yy - 1)^2= ((x + 1)(x - 1) + yy)^2= ((2 + 2cosθ - 2(cosθ)^2)(2cosθ - 2(cosθ)^2) + yy)^2= (4(cosθ + (sinθ)^2)(cosθ - (cosθ)^2) + yy)^2= (4(cosθ + (sinθ)^2)cosθ(1 - cosθ) + yy)^2= (4(cosθ + (sinθ)^2)cosθ(1 - cosθ) + 4(sinθ)^2(1 - cosθ)^2)^2= 16(((cosθ)^2 + cosθ(sinθ)^2)(1 - cosθ) + (sinθ)^2(1 - cosθ)^2)^2= 16((1 - cosθ)((cosθ)^2 + cosθ(sinθ)^2 + (sinθ)^2 -cosθ(sinθ)^2))^2= 16((1 - cosθ)((cosθ)^2 + (sinθ)^2))^2= 16(1 - cosθ)^24((x - 1)^2 + yy)= 4((2cosθ - 2(cosθ)^2)^2 + 4(sinθ)^2(1 - cosθ)^2)= 4(4(cosθ)^2(1 - cosθ)^2 + 4(sinθ)^2(1 - cosθ)^2)= 16((cosθ)^2(1 - cosθ)^2 + (sinθ)^2(1 - cosθ)^2)= 16(1 - cosθ)^2(xx + yy - 1)^2 = 4((x - 1)^2 + yy)`

--

--

--

## More from Golden Thumb

1-on-1 tutor of chosen kids

Love podcasts or audiobooks? Learn on the go with our new app.

## How to Hard Reset LG V510 G Pad 8.3 Google Play Edition ## How to automate expense tracking with Parser ## Is it better to use free and open source components or paid components or develop from scratch for… ## How to Create a Free Azure Account Step by Step ## Internal Release Notes ## Part 2: Processing Data with Java SE 8 Streams  ## Golden Thumb

1-on-1 tutor of chosen kids

## Class 10 and 12 Exam Updates: Supreme Court Refuses to Cancel Offline Board Exams ## What’s on Jim’s Mind (Issue #72) 